Jones Fractures in Sumo Wrestlers: Three Case Reports - Takashi Hoshino; Tomohiko Tateishi; Tsuyoshi Nagase; Arata Yuki; Teruhiko Nakagawa; Masamitsu Tsuchiya (Case Reports in Orthopedics)
Jones fractures sometimes occur in athletes and are known to have complications, such as nonunion, delayed union, and recurrence, even with treatment. We describe three cases of Jones fractures in sumo wrestlers with treatment-related difficulties. All patients discontinued treatment at their own discretion. The two conservative cases had nonunion or delayed union, and the operative case had a broken screw. However, all patients continued sumo wrestling, with little impact on their careers. The risk factors of Jones fractures in sumo wrestling may be heavy weight, and training or competition characteristics unique to sumo wrestling. In cases of a complete Jones fracture, operative treatment is most commonly selected, as the risk for nonunion or refractures is less than that for conservative treatment. However, in the case of sumo wrestlers, there are risks of infection and problems with treatment compliance. As taking a rest may result in a lowered rank, completing a sufficient duration of treatment is difficult. Treatment is difficult and controversial in sumo wrestlers; all three patients discontinued treatment of their own accord. These cases suggest that it is important to thoroughly inform sumo wrestlers of the treatment options, and to decide the most appropriate treatment method for each patient.